Analysis of a convective rainstorm in southern Henan caused by the cold air from the boundary layer - Lulu WANG; Haosong JIA; Jing LIU (暴雨灾害, 2023)
Using routine meteorological observations, surface encrypted observations, FY-4A satellite images, doppler radar products, and ERA5 reanalysis data, a convective rainstorm caused by the cold air from the boundary layer in southern Henan on 14 June 2021 was analyzed. The results indicate that this process occurred under the situation of southwest-westerly airflow above 850 hPa. The cold air in the boundary layer intruded into southern Henan, and the wind field formed cyclonic shear and convergence. During the process, the water vapor and thermal conditions were favoring, and the dynamic forcing is mainly located in the boundary layer. The precipitation process can be divided into two stages. The triggering and evolution stage of the convection is from 18:00 BT 14 to 00:00 BT 15. The ground-based mesoscale convergence line formed by the southward movement of cold air moved southward to southern Henan, triggering quasi-linear convection, and then the convergence line broke. The convergence line in eastern Zhumadian further moved southward, and the convection weakened accordingly. The wind field in the Nanyang Basin formed a mesoscale cyclonic rotation and convergence, where the convection was maintained. The second stage is the re-enhancement and maintenance of convection from 00:00 BT to 06:00 BT 15. As the cold air near the ground intensifies again, the convection from Nanyang to the west of Zhumadian intensifies and moves slowly. A mesoscale cyclonic convergence center was formed near the Nanyang Station and maintained for a long time, which is conducive to the continuous generation and eastward movement of convection here. The convergence and uplift of wind field from the topography of the bell mouth in western Zhumadian also favored the maintenance of convection.